Does industry matter? Drivers and barriers for open innovation in high-tech and non-high-tech industries. Evidence from Poland - Patryk Dziurski; Agnieszka Sopińska (International Journal of Management and Economics, 2020)
Firms adopt open innovation for different reasons, and they experience various barriers for open innovation. Thus, the paper aims to answer two questions: (1) what type of drivers and barriers for open innovation that are to be identified among innovative firms in Poland and (2) what kind of differences in motives and barriers between high-tech and non-high-tech industries can be identified. The authors analyzed drivers and barriers for open innovation drawn from a survey database of on 122 innovative firms in Poland by means of the CATI method. The study confirms that the concept of open innovation is adopted in high-tech as well as non-high-tech industries. The study also shows that the most important drivers in high-tech and non-high-tech industries are market-driven motives, whereas the most important barriers are related to legal and financial factors. Moreover, the research does not confirm that there are different drivers and barriers between in high-tech and non-high-tech industries.
Keywords: O31; O32; O36; 650; open innovation; drivers for open innovation; barriers for open innovation; high-tech industries; non-high-tech industries